2021
DOI: 10.1186/s12913-021-06735-3
|View full text |Cite
|
Sign up to set email alerts
|

Delivering an efficient and effective support group for patients with implantable cardioverter-defibrillators (ICDs): patient perspectives of key concerns and predictors of inclination to attend

Abstract: Background A subset of patients experience psychological distress following insertion of an implantable cardioverter-defibrillator (ICD) and ICD support groups are recommended, however access to these groups is limited. This study aimed: to gauge a better understanding of patients’ key ICD-related concerns; to determine patient interest in a support group and topics deemed helpful to address in a support group; and to examine factors which affect patient inclination to attend. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Most included studies were based in the USA, and it is striking that no Western European studies were found. A recent UK study44 commented that while there is interest in patient support groups, there are not many. Perhaps even more important is the fact that ICD implant rates in the USA have historically been 4–5 times higher than in Europe 45.…”
Section: Discussionmentioning
confidence: 99%
“…Most included studies were based in the USA, and it is striking that no Western European studies were found. A recent UK study44 commented that while there is interest in patient support groups, there are not many. Perhaps even more important is the fact that ICD implant rates in the USA have historically been 4–5 times higher than in Europe 45.…”
Section: Discussionmentioning
confidence: 99%